Hypoxia and hypercapnia effects on cerebral oxygen saturation in avalanche burial: A pilot human experimental study - Strapazzon, Giacomo; Gatterer, Hannes; Falla, Marika; Dal Cappello, Tomas; Malacrida, Sandro; Turner, Rachel; Schenk, Kai; Paal, Peter; Falk, Markus; Schweizer, Jürg; Brugger, Hermann (Resuscitation, 2021)
A sufficient supply of oxygen is crucial to avoid hypoxic cardiac arrest and brain damage within 30 min in completely-buried avalanche victims. Snow density influences levels of hypoxia and hypercapnia. The goal of this study was to investigate the effects of hypoxia and hypercapnia on cerebral oxygenation (ScO2) in humans breathing into an artificial air pocket. Each subject breathed into a closed system (air-tight face mask – plastic tube – snow air-pocket of 4 L) up to 30 min. Each subject performed three tests in different snow densities. ScO2 was measured by a near-infrared spectroscopy (NIRS) device. Measurements included peripheral oxygen saturation (SpO2), end-tidal carbon dioxide (ETCO2), air pocket gases and blood gases. Snow density was assessed via standard methods and micro-computed tomography. Based on predetermined criteria, tests were classified based on whether they were terminated before 30 min and the reason for termination. The categories were: completed tests (30 min), tests terminated before 30 min when SpO2 dropped to ≤75% and tests that were terminated before 30 min by requests of the subjects. General linear models were used to compare termination groups for changes in ScO2, ETCO2, SpO2 and air pocket gases, and a multivariate analysis was used to detect factor independent effects on ScO2. ScO2 was decreased in the group in which the tests were terminated for SpO2 ≤ 75% caused by a decrease in oxygen supply in high snow densities. In the completed tests, an increase in ScO2 occurred despite decreased oxygen supply and decreased carbon dioxide removal. Our data show that ScO2 determined by NIRS was not always impaired in humans breathing into an artificial air pocket despite decreased oxygen supply and decreased carbon dioxide removal. This may indicate that in medium to low snow densities brain oxygenation can be sufficient, which may reflect the initial stage of the triple H (hypothermia, hypoxia, and hypercapnia) syndrome. In high snow densities, ScO2 showed a significant decrease caused by a critical decrease in oxygen supply. This could lead to a higher risk of hypoxic cardiac arrest and brain damage.